Content regulation in Malaysia: enforcing the laws governing online obscene materials / 'Adil Safwan Ahmad Shaffie, 'Atif Hilmi Abdullah and Muhammad Zulfikri Mohamed Nasir - Ahmad Shaffie, 'Adil Safwan; Abdullah, 'Atif Hilmi; Mohamed Nasir, Muhammad Zulfikri (2012)
This research mainly focuses on the issue of content regulation and the use of the enforcement of the laws in governing online obscene materials in Malaysia. This research deals with the issue of the enforcement of both the traditional and specific laws in curbing online obscene materials. The traditional law include the Penal Code whereas the specific laws and guidelines are the Communications and Multimedia Act 1998, the Malaysian Communications and Multimedia Content Code. The series of literature are reviewed as we compare the laws in Malaysia with the laws in other countries including the United Kingdom and China. From the literature review as well as the background of this research, it is evident that the question of content regulations in Malaysia is the issue which has become a national agenda. The number of obscene contents on the internet had been increasing in a catastrophic rate. The challenges and the problems of implementing and enforcing the content regulations are demonstrated in regulating in this research. This study hopes to assist the policy maker in improving the level of enforcement of content regulation in regulating obscene materials on the Internet in Malaysia.